Suspected bacterial ventriculitis in a nine-month-old Goldendoodle - Loubser, L C; Botha, W J; le Roux, C (Journal of the South African Veterinary Association, 2024)
Bacterial ventriculitis is an uncommon, often fatal complication of intracranial bacterial infection. This case report describes a nine-month-old spayed female Goldendoodle that presented with a history of acute onset generalised seizures. The initial clinical examination, neurological examination and minimum database laboratory tests were unremarkable, and the dog was diagnosed with probable idiopathic epilepsy. Three weeks thereafter, the patient developed breakthrough clustering orofacial and generalised seizures. Magnetic resonance imaging (MRI) findings were consistent with bacterial ventriculitis. Broad-spectrum antibiotic and supportive therapy was initiated pending cerebrospinal fluid (CSF) analysis, serology and bacterial culture; however, the patient died eight hours after initiating treatment. To our knowledge, this is the first case report of suspected bacterial ventriculitis in a dog in South Africa and describes its atypical clinical presentation, progression and unique MRI findings.